Exploring new netting material for fishing: the low light level of a luminous netting negatively influences species separation in trawls. (28th August 2021) - Karlsen, Junita Diana; Melli, Valentina; Krag, Ludvig Ahm
Abstract: We tested if a newly developed luminous netting, VISIONET, could change the vertical behaviour of six commercially important species in a Nephrops ( Nephrops norvegicus ) trawl fishery. We inserted a V-shaped piece of VISIONET ascending on each side of the tapered section just ahead of a divided codend. The length-based effect on the vertical separation of fishes and Nephrops was quantified, and we evaluated if the presence of VISIONET had the potential to increase the fish capture in the upper compartment. Contrary to our expectation, gadoids entered the lower compartment more frequently than in the control trawl. This was similar to that previously found when applying green LED lights in the tapered section, however opposite for haddock ( Melanogrammus aeglefinus ). The flatfishes did not respond. Large Nephrops significantly increased their preference for the lower compartment. Our results show that low intensity light is sufficient to alter the vertical distribution of both fishes and Nephrops . Responses of fishes to different variables, including light intensities, need to be studied in more detail to understand the underlying mechanisms and to ultimately reduce unwanted catch more efficiently. Luminous netting can be integrated in any given trawl design and does not require batteries or electronics.